Predicting cortical bone strength from DXA and dental cone-beam CT. - Jui-Ting Hsu (Public Library of Science (PLoS), 2012)
Objective This study compared the capabilities of dual-energy X-ray absorptiometry (DXA) and dental cone-beam computed tomography (CBCT) for predicting the cortical bone strength of rat femurs and tibias. Materials and methods Specimens of femurs and tibias obtained from 14 rats were first scanned with DXA to obtain the areal bone mineral density (BMD) of the midshaft cortical portion of the bones. The bones were then scanned using dental CBCT to measure the volumetric cortical bone mineral density (vCtBMD) and the cross-sectional moment of inertia (CSMI) for calculating the bone strength index (BSI). A three-point bending test was conducted to measure the fracture load of each femur and tibia. Bivariate linear Pearson analysis was used to calculate the correlation coefficients (r values) among the CBCT measurements, DXA measurements, and three-point bending parameters. Results The correlation coefficients for the associations of the fracture load with areal BMD (measured using DXA), vCtBMD (measured using CBCT), CSMI (measured using CBCT), and BSI were 0.585 (p = 0.028) and 0.532 (p = 0.050) (for the femur and tibia, respectively), 0.638 (p = 0.014) and 0.762 (p = 0.002), 0.778 (p = 0.001) and 0.792 (p<0.001), and 0.822 (p<0.001) and 0.842 (p<0.001), respectively. Conclusions CBCT was found to be superior to DXA for predicting cortical bone fracture loads in rat femurs and tibias. The BSI, which is a combined index of densitometric and geometric parameters, was especially useful. Further clinical studies are needed to validate the predictive value of BSI obtained from CBCT and should include testing on human cadaver specimens.